Steroid hormone levels and bone mineral density in women over 65 years of age - Nunes, Elsa (2023)
Previous studies using immunoassays for steroid measurements have focused on the association between steroid hormone levels and bone mineral density (BMD) in postmenopausal women, obtaining contradictory results. This study aimed to assess this association using a highly sensitive bioanalytical method. A total of 68 postmenopausal women, aged 65–89 years, were enrolled in a crosssectional study. Measurements of the BMD of the hip and lumbar spine were performed using dual energy Xray absorptiometry, and serum hormone levels were quantifed by gas chromatography and tandem mass spectrometry. Associations between estradiol (E2), testosterone, dehydroepiandrosterone (DHEA), androstenedione and T score levels of the hip and lumbar spine were evaluated, after adjustment for confounding variables. The analysis revealed a statistically signifcant association between testosterone and the T score of the hip (p= 0.035), but not that of the lumbar spine. No statistically signifcant associations were found between E2, DHEA, androstenedione and the T scores of the hip and the lumbar spine. Using a highly sensitive hormone assay method, our study identifed a signifcant association between testosterone and BMD of the hip in women over 65 years of age, suggesting that lower testosterone increases the risk of osteoporosis.